Smoking cessation aids and strategies: a population-based survey of former and current smokers in Norway - Marianne Lund; Ingeborg Lund (BMC, 2022)
Abstract Background In Norway, tobacco consumption is equally divided between combustible (cigarettes) and non-combustible (snus) tobacco. In the process of quitting, people who smoke can choose between several smoking cessation aids and strategies based on what is available on the market or what are recommended as cessation aids. A quit attempt may be planned or unplanned and consist of a gradual decline in consumption or an abrupt quitting. This study explores smoking cessation aids and strategies used at the latest quit attempt among people who have ever smoked. How prevalent is the use of various cessation aids and strategies, and do they correlate with each other? Are there any differences in successful quits depending on the use of a specific cessation aid or strategy? Method We used repeated cross-sectional representative surveys in Norway for 2017, 2018, 2019 and 2020. The analytic sample consists of people aged 20 years or older who have ever smoked daily, more precisely current daily smokers with at least one quit attempt (n = 476), and former daily smokers who quit in 2012 or later (n = 397). Participants answered questions on cessation aids and strategies used at their last quit attempt. Logistic regression analysis was used to estimate the associations between cessation aids and strategies and sociodemographic and smoking-related variables and successful quit attempts. Results Fifty-six percent of people who ever smoked daily reported any use of cessation aids, and nicotine replacement therapy (NRT), snus and e-cigarettes were the most commonly used cessation aids. Snus and web/mobile use was associated with successful quits, while NRT was associated with unsuccessful quit attempts. When exclusive use was separated from the combined use of several aids, only snus was associated with successful quits. Conclusion Snus use was found to be a "stand-alone" cessation aid, and only weakly associated with the use of other cessation aids. Further investigation of cessation aid preferences is needed, especially among smokers with little or no contact with health services and/or for whom traditional cessation aids have no appeal.